Sustainability and Value in Urban Development: Business Models Between Green Growth and Degrowth - Intan Farhana; Nabilah (Global Financial Accounting Journal, 2026)
Urban sustainability is increasingly challenged by ecological degradation and social inequality, while dominant development models centered on economic growth have proven inadequate in addressing these issues. This paper examines the potential of socially innovative business models and the sharing economy as alternative approaches to sustainable urban development. Specifically, it considers whether these models can contribute to the Sustainable Development Goals (SDGs) when assessed through the lens of post-growth and degrowth thinking. Drawing on a conceptual and qualitative approach, the paper is based on an extensive review of literature in sustainable development, social innovation, and urban post-growth economics. The analysis focuses on how alternative business models reshape urban economic practices by reframing value creation and redistribution beyond profit-oriented logics. While these models hold potential, they remain vulnerable to being shaped by neoliberal agendas, which may limit their transformative capacity. The paper argues that their effectiveness depends on inclusive governance, ethical foundations, and institutional mechanisms that support long-term social and ecological priorities. Without these, such initiatives risk remaining symbolic. The study concludes that to support meaningful urban transformation, these models must be embedded within broader regulatory changes, public procurement reforms, and sustainability metrics that reflect non-financial forms of value.